ANALISIS INSTRUMEN TEST ANALISIS KUALITAS INSTRUMEN TES SOAL UJIAN AKHIR SEMESTER GENAP MATA PELAJARAN KIMIA KELAS XI ILMU PENGETAHUAN ALAM SEKOLAH MENENGAH ATAS NEGERI 6 PEKANBARU TAHUN AJARAN 2015/2016: ANALISIS INSTRUMEN SOAL - Tengku, Syarifah Wikasari (Jurnal Riset Pendidikan Kimia (JRPK), 2024)
There were many factors causing problems encountered in the learning process, one of them was the learning instrument used and created by the teacher. Learning instrument can be as test items. This research aimed at knowing the quality of test items of final examination of the second semester on Chemistry subject of XI Natural Science at State Senior High School 6 Pekanbaru in the Academic Year of 2015/2016 in terms of qualitative and quantitative aspects. Sample of this research was all student answer sheets of XI Natural Science (XI Natural Science 1 to 6) comprised 192 students. Test items of final examination of the second semester comprised 30 multiple choice questions. Research findings showed inappropriate test items in term of qualitative aspect, there were 8 (26.7%) test items in term of material, 12 (40%) test items in term of construction, and 23 (76.6%) test items in term of language. Whereas in the quantitative aspect, 3 (10%) test items were not valid. High reliability test items were 0.72. In term of discriminator, there were 3 (10%) test items were on bad category, 11 (36.7%) test items were on medium category, and 16 (53.3%) test items were on good category. In term of difficulty level, there were 2 (6.9%) test items were on difficult category, 22 (72.4%) test items were on medium category, and 6 (23%) test items were on easy category. 27 (23%) options of distractors were not working. It could be concluded that the percentage of inappropriate test items in qualitative aspect was 47.7% meaning that the quality of test items was enough. In quantitative aspect validity, reliability, and discriminator were on good criteria, whereas difficulty level and distractor were on enough criterion.